Unlocking Basketball Athletic Performance: Force Plate-Derived Countermovement Jump Normative Reference Values From Seven NCAA Division-I Power Five Men's College Basketball Teams - Drake Berberet; Adam Petway; Karah Bell; Zack Gillen; Peter Mundy; Henry Barrera; Jason Kabo; Dom Walker; Garrett Medenwald; Braden Welsh; John Mcmahon (International Universities Strength and Conditioning Association, 2024)
This study represents a pioneering effort in establishing normative benchmarking for countermovement jump (CMJ) metrics on Hawkin Dynamics dual wireless force plate within a substantial cohort (n = 96) of NCAA Division-I (DI) Power Five Men's College Basketball (MCBB) players. This cohort comprised four centers (age = 20.01 ± 1.31 years, height on website = 216.32 ± 5.27 cm, body mass on plates = 115.11 ± 16.13 kg), 37 forwards (age = 21.09 ± 1.68 years, height on website = 203.84 ± 5.45 cm, body mass on plates = 103.67 ± 10.42), and 55 guards (age = 20.92 ± 1.54 years, height on website = 190.49 ± 7.44 cm, body mass on plates = 87.04 ± 6.98 kg) from seven teams that performed three CMJ trials with hands on hips during the pre-season period of the 2023-2024 season over a span of 26 days and seven testing sites. All data was uniformly collected by a single designated tester who implemented consistent instructions, procedures, and equipment at all test sites. Comparing forwards and guards, 45% (18/40) of the reported metrics showed significance (p < 0.05) and 35% (14/40) yielded moderate-large effect sizes (e.g., > 0.50). Additionally, percentiles (3-97th) with qualitative descriptors and a traffic light system were provided. Such normative data can serve as a valuable reference point for coaches, scouts, and players alike, facilitating the evaluation of both individual and team performance while also guiding the development of tailored strength and conditioning strategies specific to the demands of NCAA DI MCBB.